Empowering Students as Agents of Religious Moderation in Islamic Higher Education Institutions - Mustakim, Zaenal; Ali, Fachri; Kamal, Rahmat (Jurnal Pendidikan Islam, 2021)
Promoting moderate Islam in the education sector to prevent radicalism and violent extremism, particularly in Indonesiaâ€™s Islamic universities has been considered important. This study demonstrated how values of moderate Islam empower student to prevent radicalism and violent extremism in university. This research is qualitative case study. Eight students and two teachers at a public Islamic university in Central Java, Indonesia were recruited to participate. Data were collected through semi-structured interviews and observation. The result of the study shows that the values of tolerance, inclusivity, flexibility, and objectivity in understanding religious texts were internalized to empower students as agents of religious moderation. The presentation of learning materials were adopted from national journals, reputable international journals, websites, and official social media platforms for moderate Muslim intellectuals. The materials contributed significantly to the prevention of hate speech and hoaxes. Â